Urban expansion induced land use changes and its effect on ecosystem services in Addis Ababa, Ethiopia - Hailu, Tadesse; Assefa, Engdawork; Zeleke, Tesfaye (Frontiers in Environmental Science, 2024)
The study examines the dynamics of urban expansion and changes in land use in Addis Ababa from 1993 to 2023 using satellite data and GIS analysis, as well as the benefit transfer approach for valuing ecosystem services. In addition, an expert survey was conducted using the analytical hierarchy process (AHP) method to determine the factors driving urban expansion. Results reveal oscillations in urban expansion rates and intensities over the three-decade period. While the 2003–2013 decade witnessed rapid urban growth, subsequent years showed a slowdown. The overall period (1993–2023) has an intensity index greater than 1, indicating that urban areas expanded faster than the city’s overall growth during the entire time frame. Land cover analysis revealed a significant decrease in green areas and croplands and a remarkable increase in built-up areas. In aggregate, the natural land cover was reduced by 128.6% whereas built-up increased by 224.7%. This shift signifies a transition from natural and agricultural land uses to urbanization and development. Moreover, the study evaluates changes in ecosystem service values (ESVs), indicating a consistent decline over time, particularly in forestlands and urban green areas. The significant alteration in land use that built up caused to ecosystems has resulted in an annual loss of 90.7 million USD from 1993 to 2023 in terms of ecosystem service value. The most significant impacts were observed in food production, climate regulation, and habitat ecosystem services. The encroachment of built-up areas on different land use categories leads to substantial losses in ecosystem service values. Socioeconomic factors, notably population growth and migration, emerge as primary drivers of urban expansion, emphasizing the interconnectedness of demographic changes and land use patterns. Overall, the findings underscore the complex interplay between urban expansion, land use dynamics, and ecosystem services in Addis Ababa, highlighting the importance of informed urban planning and policy interventions to mitigate adverse environmental impacts.